1974
DOI: 10.1037/h0037489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternative positioning of open-ended questions in multiple-choice questionnaires.

Abstract: Two studies investigated the effect of the placement of open-ended questions, relative to multiple-choice questions, on the responses elicited. Both studies found that positionings at both the beginning and the end of a predominantly multiple-choice questionnaire elicited significantly more responses than did either placement alone. When the two positions were used singly, the one at the beginning was found to elicit more discrete ideas and response categories. This was true for black samples and white samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 1 publication
0
13
1
Order By: Relevance
“…Clearly, if the dynamics of the survey interview are as proposed, it is not at all surprising that these results differ from those obtained by Johnson et al (1974); the results reported here were obtained from face-to-face interviews of a random cross-section of adults, whereas theirs were obtained through self-completion questionnaires administered to university undergraduates in an introductory psychology class on a very different set of topics. Indeed, this very difference in experimental results highlights the importance of the social situation on responses to open-ended questions.…”
Section: Interpretation: the Dynamics Of The Survey Interviewcontrasting
confidence: 38%
See 1 more Smart Citation
“…Clearly, if the dynamics of the survey interview are as proposed, it is not at all surprising that these results differ from those obtained by Johnson et al (1974); the results reported here were obtained from face-to-face interviews of a random cross-section of adults, whereas theirs were obtained through self-completion questionnaires administered to university undergraduates in an introductory psychology class on a very different set of topics. Indeed, this very difference in experimental results highlights the importance of the social situation on responses to open-ended questions.…”
Section: Interpretation: the Dynamics Of The Survey Interviewcontrasting
confidence: 38%
“…College students have been shown to give fewer answers to open-ended questions towards the end of a long interview (Johnson et al, 1974). Furthermore, respondents appear more prone to response sets in batteries of items with similar response scales when these appear towards the end of the questionnaire, especially on subject matters of low interest to them (Herzog and Bachman, 1978).…”
Section: The Literaturementioning
confidence: 99%
“…The theory of satisficing predicts that reduced participant motivation should be especially likely to yield increased satisficing as participant fatigue grows toward the end of a long questionnaire, as evidenced by numerous studies (Backor, Golde, & Nie, 2007;Herzog and Bachman, 1981;Johnson, Sieveking, & Clanton, 1974;Kraut et al, 1975). Therefore, if complete anonymity reduces participant motivation to provide accurate reports, then complete anonymity may yield more evidence of satisficing at the end of a questionnaire than at the beginning.…”
Section: The Present Investigationmentioning
confidence: 99%
“…Close ended test items can be presented in various ways, namely, multiple choice questions (MCQ), fill-in the missing words, matching the columns etc. [12]. Some other broad categories of test items are TruelFalse, Assertion-Reason questions (combines elements of MCQ and true-false), multiple response questions (MRQs) (similar to MCQs, but involve the selection of more than one answer from a list), graphical hot-spot questions (involving selecting an area(s) of the screen) text/numerical questions (involving the input of text or numbers at the keyboard), column matching, sore fmger questions, ranking questions, sequencing (to position text or graphic objects in a given sequence., etc.…”
Section: Learners Response In An E-learning Environmentmentioning
confidence: 99%